Pengaruh Suplementasi Vitamin E, Mineral Selenium dan Zink Terhadap Konsumsi Nutrien, Produksi dan Kualitas Semen Sapi Simental - Fitrah Khairi; Anis Muktiani; Yon Supri Ondho (Agricultural Faculty, 2014)
(Effect of supplementation of vitamin E, Selenium and Zinc mineral againstto nutrient consumption, production and quality cement simental cow)ABSTRACT. Simental bulls often experience a decline in production and semen quality in the rainy season, which have a higher humidity and high rainfall. This study aims to maintain nutrient consumption, production and semen quality Simental bulls during the rainy season through the supplementation of Vitamin E, Selenium and Zinc Minerals. The study was conducted in July-December 2012 at the Artificial Insemination Center (BIB) Unggaran. The research material used in this study were 12 males Simental cows BIB Unggaran grouped by age. The experimental design used in this study is a randomized block design (RBD) with 3 treatments T1 (ration + Vit. E), T2 (ration + Vit. E + Se), T3 (ration + Vit. E + Se + Zn) and 4 groups as replicates. Parameters measured were dry matter intake and nutrient consumption, production and semen quality. Cement production was measured from fresh semen volume during the study, whereas semen quality measured motility and concentration of spermatozoa from fresh semen. Data consumption of dry matter and nutrient intake obtained were processed using analysis of variance, followed by Duncan test. While data on production and semen quality were analyzed descriptively. The results showed that the combination of vitamin E supplementation, minerals Selenium and Zinc did not affect dry matter intake, total digestible nutriens and crude protein, but resulted in a decrease in the percentage of shelter, semen volume, sperm motility and concentration smaller than before treatment. Treatment T1, T2 and T3 resulted in a decrease in the number of shelter respectively 41,55%, 19,56% and 13,63% compared to before treatment, whereas a decrease in semen volume unchanged at 44,9 %, 43,7% and 40,99%. Sperm motility due to treatment T1, T2 and T3 respectively decreased by 55,87%, 22,10% and 13,63% compared to before treatment. In line with sperm motility, sperm concentration in treatment T , T2 and T3, respectively decreased by 49,16%, 22,85% and 14,88%. The conclusion is a combination of vitamin E supplementation, minerals Selenium and Zinc can prevent the decline in cement production, sperm motility and sperm concentration Simental bulls during the rainy season.